Respuesta :
Hello,
After decrypting the question:
f(x)=2x^4-4x^3-11x^2+3x-6
f(-2)=2(-2)^4-4(-2)^3-11(-2)^2+3*(-2)-6=2*16+32-44-6-6=8
After decrypting the question:
f(x)=2x^4-4x^3-11x^2+3x-6
f(-2)=2(-2)^4-4(-2)^3-11(-2)^2+3*(-2)-6=2*16+32-44-6-6=8
Answer:
The value of f(x) is 8 at x=-2.
Step-by-step explanation:
The given function is
[tex]f(x)=2x^4-4x^3-11x^2+3x-6[/tex]
We have to find the value of function at x=-2.
Substitute x=-2 in the given function.
[tex]f(-2)=2(-2)^4-4(-2)^3-11(-2)^2+3(-2)-6[/tex]
[tex]f(-2)=32+32-44-6-6[/tex]
[tex]f(-2)=64-56[/tex]
[tex]f(-2)=8[/tex]
Therefore the value of f(x) is 8 at x=-2.